1975
DOI: 10.1177/00220345750540021901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Conditioning with Fluoride and Phosphoric Acid on Enamel Surfaces as Evaluated by Scanning Electron Microscopy and Fluoride Incorporation

Abstract: The etching effect of 50% H-3PO-4 applied together with 2% NaF or SnF-2 was compared with the effect of H-3PO-4 on pre- and postfluoridated enamel by scanning electron microscopy. Substantial etching of enamel resulted with use of 50% H-3PO-4 with 2% NaF. High fluoride incorporation in the surface provided additional protection of the conditioned enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Gwinnett (1971) who studied the histological changes in human enamel after treatment with 50% phosphoric acid found that the thickness of the removed surface layer was 5-25 yttm. The fact that no significant differences of fluoride were found between unetched and etched enamel layers in the present and previous study confirms that etching with 50 % phosphoric acid removes only a very thin layer of the surface (Kochavi et al, 1975). The inclusion of fiuoride compounds in 50% phosphoric acid noticeably mcreased the fiuoride concentration of the etched enamel (Table I).…”
Section: Discussionsupporting
confidence: 86%
“…Gwinnett (1971) who studied the histological changes in human enamel after treatment with 50% phosphoric acid found that the thickness of the removed surface layer was 5-25 yttm. The fact that no significant differences of fluoride were found between unetched and etched enamel layers in the present and previous study confirms that etching with 50 % phosphoric acid removes only a very thin layer of the surface (Kochavi et al, 1975). The inclusion of fiuoride compounds in 50% phosphoric acid noticeably mcreased the fiuoride concentration of the etched enamel (Table I).…”
Section: Discussionsupporting
confidence: 86%
“…These products partly or completely fill the interprismatic space and result in a smaller bonding area as well. 22 Therefore, the decrease in tensile bond strength for the fluoride prophylactic paste group is most likely due to decreased enamel solubility after the incorporation of the fluoride ions onto the enamel surface. The smooth cement-enamel interface observed in the SEM may indicate reduced retention and mechanical interlocking ( Figure 2B).…”
Section: Discussionmentioning
confidence: 99%
“…Restorative dentists have also found bonding to fluorosed teeth to be problematic. 3 Scanning electron microscope studies have confirmed that the difficulty in bonding is likely attributable to the inability of fluorosed enamel to be effectively etched with 37% phosphoric acid, [4][5][6] which results in a decreased amount of enamel irregularity, preventing effective bonding. These studies demonstrate that it is difficult to predict how a fluorosed tooth will be etched.…”
Section: Introductionmentioning
confidence: 99%